The Impact of Growth on the Transmission of Patience - Domenico Delli Gatti; Jakob Grazzini; Domenico Massaro; Fabrizio Panebianco (Center for Economic Studies and ifo Institute (CESifo), 2022)
Patience affects economic growth, no news. This paper investigates the opposite causal relationship, i.e., how growth influences patience. We propose a simple theoretical framework where heterogeneous parents may choose to transmit their cultural trait - patience - to their offspring. Our model shows that parental effort to educate children to patience positively depends on economic growth. We test empirically this result using both country-level and individual data and show that, coherently with the model's prediction, growth has a significant impact on the effort to teach patience.
Keywords: D15; D91; E21; O47; 330; growth; patience; cultural transmission